2021
DOI: 10.1186/s12906-021-03328-9
|View full text |Cite
|
Sign up to set email alerts
|

The polyphenol/saponin-rich Rhus tripartita extract has an apoptotic effect on THP-1 cells through the PI3K/AKT/mTOR signaling pathway

Abstract: Background Hyperactivation of mechanistic target of rapamycin (mTOR) signaling pathway is involved in the regulation of cellular growth, proliferation, and more in general, is a common phenomenon in most types of cancers. Thus, natural substances targeting this pathway can be of great therapeutic potential in supporting the treatment of tumor patients. Rhus tripartita (Ucria) Grande is a plant growing in desertic areas which is traditionally used for the treatment of several diseases in Tunisia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…These results demonstrated that bisdesmosidic compounds ( 2–4 ) did not show any cytotoxic activity while following monodesmosidic compounds ( 1 , 2a , 3a , and 4a ) have cytotoxic effect on cancerous cell lines. In literature, as a similar study Tlili et al 31 , who identified the biochemical profiles of the major compounds found in plant leaf extract and examined its anti-leukemic potential against acute monocytic leukemia (AML) THP-1 cells. They proved that the mTOR pathway may be involved in cell cycle inhibition and apoptosis induction caused by saponin.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that bisdesmosidic compounds ( 2–4 ) did not show any cytotoxic activity while following monodesmosidic compounds ( 1 , 2a , 3a , and 4a ) have cytotoxic effect on cancerous cell lines. In literature, as a similar study Tlili et al 31 , who identified the biochemical profiles of the major compounds found in plant leaf extract and examined its anti-leukemic potential against acute monocytic leukemia (AML) THP-1 cells. They proved that the mTOR pathway may be involved in cell cycle inhibition and apoptosis induction caused by saponin.…”
Section: Resultsmentioning
confidence: 99%
“…PI3K/Akt intracellular signaling pathway is involved in many aspects of cellular survival and growth, in physiological as well as pathological conditions. Disruption of the PI3K/Akt pathway contributes to multiple cardiovascular diseases, such as type II diabetes, insulin resistance, hypertension, and hyperlipidemia 18–24 . PI3K signaling can be activated following a wide range of cues emanating from the plasma membrane, such as integrins, G‐protein coupled receptors (GPCR), immune receptors, receptor tyrosine kinases, and small Ras‐related GTPases.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…Disruption of the PI3K/Akt pathway contributes to multiple cardiovascular diseases, such as type II diabetes, insulin resistance, hypertension, and hyperlipidemia. [18][19][20][21][22][23][24] PI3K signaling can be activated following a wide range of cues emanating from the plasma membrane, such as integrins, G-protein coupled receptors (GPCR), immune receptors, receptor tyrosine kinases, and small Rasrelated GTPases. The binding of ligands to cellmembrane receptors (receptor tyrosine kinases or GPCR) activates PI3K.…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…Many naturally occurring anti-cancer agents have been extracted with high efficiency and recovery by UAE, such as mangiferin from Mangifera indica L. [22], taxol from Taxus mairei [23], flavonoids from Celastrus hindsii [24], and tannins and polyphenols from Pistacia lentiscus [25]. The extraction of saponins with anti-cancer activity from plants such as Curcuma angustifolia, Psidium guajava, Rhus tripartite, and Calotropis gigantea, have still not been reported from P. fruticose [26][27][28][29]. Simultaneously, response surface methodology (RSM) is also commonly employed for extraction optimization of plant-based compounds and analysis of the interactions between different factors as well as the effect of each factor on the response values.…”
Section: Introductionmentioning
confidence: 99%